Critical evaluation of Hydrogen Sulfide (H2S) when associated with corrosion, worker health and safety - Carneiro, Jackson Carolino; Mainier, Fernando B.; Mainier, Renata Jogaib; Silva, Dayanni de Brito da; Natalino, Clara do Nascimento (Seven Editora, 2023)
Hydrogen sulfide (H2S) is a colorless gas with a characteristic unpleasant odor (like rotten eggs) that is extremely toxic and corrosive. Due to its toxicity, H2S irritates the eyes and/or affects the nervous and respiratory systems. Concentrations on the order of 700 to 1500 ppm can kill a human in a matter of minutes. The media has presented several examples of H2S leaks that jeopardize human lives, threaten the integrity of industrial assets, and endanger the environment. This work aims to show the importance of knowledge of the origins and physicochemical properties of hydrogen sulfide in the direct and indirect relations with man, the environment and industrial equipment. DOI:https://doi.org/10.56238/interdiinovationscrese-046